A fictive people : antebellum economic development and the American reading public - Zboray, Ronald J. (Oxford University Press, 1993)
This text aims to explode two notions that are commonplace in American cultural histories of the 19th century: that the spread of literature was a simple force for the democratization of taste, and that there was a body of 19th-century literature that reflected "a nation of readers."